1999
DOI: 10.1136/sti.75.5.317
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus DNA on the fingers of patients with genital warts

Abstract: Objective:To determine whether patients with genital warts carry human papillomavirus (HPV) DNA on their fingers. Methods: 14 men and eight women with genital warts had cytobrush samples taken from genital lesions, finger tips, and tips of finger nails. Samples were examined for the presence of HPV DNA by the polymerase chain reaction. Results: HPV DNA was detected in all female genital samples and in 13/14 male genital samples. HPV DNA was detected in the finger brush samples of three women and nine men. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(100 citation statements)
references
References 18 publications
(6 reference statements)
1
97
0
2
Order By: Relevance
“…Furthermore, sexual practices among WSW could potentially allow for intravaginal deposition of HPV through digital-vaginal contact and shared "sex toys" 4,[13][14][15][16] ; genital HPV types have also been identified on human fingers. 17 Perhaps of equal importance, studies have shown that most WSW (53%-99%) have had sex with men and that many (21%-30%) continue to have sex with men. 18,19 Among these women, acquisition of chronic viral sexually transmitted diseases, including HPV, genital herpes, and HIV, from male partners presumably occurs at a rate per contact similar to that in heterosexual populations, and women infected via this route could serve as a source for subsequent viral transmission to their female partners.…”
mentioning
confidence: 99%
“…Furthermore, sexual practices among WSW could potentially allow for intravaginal deposition of HPV through digital-vaginal contact and shared "sex toys" 4,[13][14][15][16] ; genital HPV types have also been identified on human fingers. 17 Perhaps of equal importance, studies have shown that most WSW (53%-99%) have had sex with men and that many (21%-30%) continue to have sex with men. 18,19 Among these women, acquisition of chronic viral sexually transmitted diseases, including HPV, genital herpes, and HIV, from male partners presumably occurs at a rate per contact similar to that in heterosexual populations, and women infected via this route could serve as a source for subsequent viral transmission to their female partners.…”
mentioning
confidence: 99%
“…108 Moreover, digital self-inoculation is possible as HPV DNA was noted on the fingers of males and females positive for genital HPV. 109 Although none of the studies highlighted in this review screened for HPV-related genital disease, good personal hygiene is a reasonable starting point to minimize the risk of ocular infection.…”
Section: Discussionmentioning
confidence: 99%
“…Routes of exposure include skin-to-skin and sexual contact [40][41][42]. It follows that vaccination efficacy is maximized in individuals who are not yet sexually active and thus likely to be HPV-negative.…”
Section: Maximizing Vaccine Efficacymentioning
confidence: 99%